Polyurethane versus silicone catheters for central venous port devices implanted at the forearm. (May 2016) - Wildgruber, Moritz; Lueg, Claudia; Borgmeyer, Sebastian; Karimov, Ilham; Braun, Ulrike; Kiechle, Marion; Meier, Reinhard; Koehler, Michael; Ettl, Johannes; Berger, Hermann
Abstract: Purpose: We aimed to analyse short and long-term complications of polyurethane (PU) versus silicone catheters used in totally implantable venous-access ports (TIVAPs) implanted at the forearm. Methods: Retrospective analysis of 698 consecutively implanted TIVAPs was performed. Primary end-points were defined as rates of major complications associated with either type of central venous port catheter. Technical success rate, device service interval as well as minor complications not requiring port explantation were defined as secondary end-points. Results: A total of 698 port devices were implanted in 681 patients, 396 equipped with a PU catheter, 302 with a silicone catheter. The technical success rate was 99.9% with no major periprocedural complications. During follow-up a total of 211 complications in 146 patients were observed (1.0/1000 catheter days), 183 occurred associated with PU catheters (1.8/100 catheter days), 28 (0.3/1000 catheter days) with silicone catheters (log rank test p < 0.0001). Catheter-related bloodstream infections as well as thrombotic complications occurred significantly more frequently with PU catheters, while silicone catheters exhibited a trend towards a higher rate of mechanical failure such as disconnection or catheter rupture. Major complications requiring explantation of the device occurred more frequently with PU-based catheters (10.6%) compared to silicone catheter carrying ports (4.6%, log rank test p < 0.001). Conclusion: PU catheters are more susceptible to catheter-related infections and exhibit a higher thrombogenicity, compared to silicone catheters. Silicone catheters instead exhibit a trend towards decreased mechanical stability. Highlights: Follow-up complications after central venous port catheter placement differ dramatically between different catheter materials. Polyurethane catheters are significantly more frequently affected by thrombosis and catheter-related infection. Silicone catheters exhibit a trend towards increased mechanical instability.